Instability in Parent–Child Coresidence and Adolescent Development in Urban South Africa. Issue 1 (March 2016) - Marteleto, Letícia J.; Cavanagh, Shannon; Prickett, Kate; Clark, Shelley
Abstract : There is widespread recognition of the importance of family stability for child development. South Africa presents an interesting context in which to study the consequences of family instability because of the traditionally fluid nature of household composition due to labor migration, child fostering, and non‐marital fertility. More recently, the HIV pandemic has added another source of instability. Within South Africa, however, patterns of instability differ markedly across racial groups. We use the Cape Area Panel Study (CAPS) data to examine the implications of changes in parent–child coresidence for educational and sexual development of young South Africans. We show that changes in maternal and paternal coresidence have implications for the timing of sexual initiation for both black and coloured adolescents. Maternal and paternal transitions also lead to poorer educational outcomes for coloured adolescents, but parental disruptions are not significantly related to educational outcomes for blacks. These findings suggest that the implications of coresidential instability vary by race, reflecting racial differences with respect to cultural, social, and economic conditions.